Impact of Digital Health Technologies on Healthcare Service Quality and Patient Satisfaction - Dr. Sanjyoti Todkar; Dr. Garima Sahu; Dr. Divya Kulkarni (Journal of Asia Entrepreneurship and Sustainability, 2026)
Digital health technologies are also steadily changing health care management to facilitate the exchange of information, co-ordination of services, organizational efficiency and patient-centredness. The use of digital health technology and its effect on healthcare service quality and patient satisfaction were explored with electronic health record (EHR) interoperability as a proxy for digital-health capability. Secondary hospital-level data was used and a quantitative, cross-sectional design adopted. The analytical data set consisted of 1,000 records from 11 distinct acute-care hospitals, and included metrics for EHR interoperability, healthcare quality indicators, and patient-experience measures, all captured by HCAHPS. Descriptive, comparative and exploratory correlational analyses were used. The results indicated that 90.9% of hospitals had a positive status of EHR interoperability recorded. But 45.5% were below the national average for patient experience, showing that having digital capability does not guarantee better outcomes for patients. Other areas of performance were comparatively favourable, with 63.6% of hospitals above the national average for timeliness of care and 72.7% at the national average for effectiveness of care. Doctor communication had a relatively high mean rating, and care transition had the lowest rating of the HCAHPS dimensions. Initial exploratory correlations indicated that there were positive relationships between patient experience and overall hospital performance, but the results were not statistically significant. The results highlight the need for digital interoperability to be included in the management of service quality, staff competencies, communication, and redesign of processes in the interest of healthcare organizations' sustainable performance and satisfaction.